ANALYSIS OF CORRECTIVE MAINTENANCE MEASURES OSCILLATOR MODULE GLIDE PATH NORMARC EQUIPMENT AT PERUM LPPNPI CABANG SURABAYA - Musthofa, Luthfi; Toni; Irvan (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
One of the navigation equipment used to support aviation safety is the Instrument Landing System (ILS). ILS is an important landing aid to improve aviation safety. ILS uses a Localizer to provide horizontal guidance to pilots at a distance of 25 nautical miles from the runway. Then, the glide path equipment will provide vertical guidance to pilots at a distance of 10 nautical miles from the runway. In glide path equipment, there are various modules used, one of which is the oscillator module which functions as a frequency generator. This study aims to identify the cause of the fail alarm on the Remote Monitoring Management (RMM) indicator of glide path equipment caused by damage to the oscillator module. This research uses a qualitative descriptive research method which emphasizes understanding problems based on natural reality namely primary and secondary data. Through this research, the cause of oscillator module damage was found to be caused by a 10,000 microfarad elco type capacitor component that burned due to over voltage on the oscillator module.